Islamic Family Law and International Inheritance: An Analysis of Mixed Marriages from the Perspective of International Civil Law - Sahrul Hanafi; Nurman Akhmadi; Siah Khosyi’ah; Ahmad Fathoni (Civiliza Publishing, 2026)
Globalization has increased the number of mixed-nationality and interfaith marriages, giving rise to cross-jurisdictional legal complexities, particularly for Muslim parties. This study aims to analyze the application of the principles of Private International Law—namely, lex patriae, lex domicilii, lex loci celebrationis, and lex rei sitae—in the resolution of disputes regarding mixed-nationality marriages and international inheritance. The methodology employed is normative legal research using a comparative law approach and analysis of court decisions. The results of the study indicate that the validity of mixed marriages is determined through a combination of formal requirements based on lex loci celebrationis and substantive requirements subject to lex patriae or lex domicilii, which often conflict with Sharia norms and the public policy of the forum state. In international inheritance, the differences between the faraidh system and Western law lead to fragmentation in dispute resolution, particularly regarding immovable property governed by lex rei sitae. To reduce legal uncertainty, cross-jurisdictional marriage contracts, international wills, mandatory bequests, and asset transfers that comply with the principle of dual compliance are necessary. This study underscores the importance of harmonizing national law, religious law, and human rights